Consulting report – Amazona Chocolate - Silva Mercado, Roberto Marcio (2019)
Amazona Chocolate is a company that sells high-quality organic chocolate and other cacao derivatives. The market where it operates value these characteristics and is willing to pay a premium for them. The profitability of this business has attracted companies increasing the competition, which raised the awareness of Amazona Chocolate to be more competitive. Although, the company has been and remains profitable, it is unknown how the distribution of its costs are, for which it is not known for sure how the money is actually being spent. Based on these premises, the consulting project aimed to research and propose a costing system that would identify the costs incurred by the firm on each stage of its operations, while also allowing to improve the decision-making of the firm. Based on the literature review and the framework of Fisher and Krumwiede (2012), the consulting project proposed to elaborate a costing system composed by (a) variable and absorption costing (one complementing the other) for assigning costs to the products, (b) process costing for tracking direct product costs, (c) department cost pools to organize indirect product costs, and (d) transaction based drivers to allocate indirect costs, as it was identified through a weighted score assessment that this costing system was more suitable for Amazona Chocolate, based on its availability of resources, characteristics, and necessities. The proposed implementation plan estimates a total period of execution of 12 weeks, which was divided into three main phases: learning, communicating, and executing. The scheduled period is flexible based on the availability and time of the stakeholders; however, it should not take more time than the estimated by the consulting team. Finally, the consulting report did not consider a cost of implementation since the evaluation of the costing system took into account the limited resources of the company, nonetheless, it is recommended to assign a person to execute the process of digitalization of the information held in physical files, for which it was estimated a period of 15 days and an investment of S/800.